Routing and Mobility on IPv6 over LoWPAN - Oliveira, Luís Miguel Lopes de (2018)
The IoT means a world-wide network of interconnected objects based on standard communication protocols. An object in this context is a quotidian physical device augmented with sensing/actuating, processing, storing and communication capabilities. These objects must be able to interact with the surrounding environment where they are placed and to cooperate with neighbouring objects in order to accomplish a common objective. The IoT objects have also the capabilities of converting the sensed data into automated instructions and communicating them to other objects through the communication networks, avoiding the human intervention in several tasks. Most of IoT deployments are based on small devices with restricted computational resources and energy constraints. For this reason, initially the scientific community did not consider the use of IP protocol suite in this scenarios because there was the perception that it was too heavy to the available resources on such devices. Meanwhile, the scientific community and the industry started to rethink about the use of IP protocol suite in all IoT devices and now it is considered as the solution to provide connectivity between the IoT devices, independently of the Layer 2 protocol in use, and to connect them to the Internet. Despite the use of IP suite protocol in all devices and the amount of solutions proposed, many open issues remain unsolved in order to reach a seamless integration between the IoT and the Internet and to provide the conditions to IoT service widespread. This thesis addressed the challenges associated with the interconnectivity between the Internet and the IoT devices and with the security aspects of the IoT. In the interconnectivity between the IoT devices and the Internet the problem is how to provide valuable information to the Internet connected devices, independently of the supported IP protocol version, without being necessary accessed directly to the IoT nodes. In order to solve this problem, solutions based on Representational state transfer (REST) web services and IPv4 to IPv6 dual stack transition mechanism were proposed and evaluated. The REST web service and the transition mechanism runs only at the border router without penalizing the IoT constrained devices. The mitigation of the effects of internal and external security attacks minimizing the overhead imposed on the IoT devices is the security challenge addressed in this thesis. Three different solutions were proposed. The first is a mechanism to prevent remotely initiated transport level Denial of Service attacks that avoids the use of inefficient and hard to manage traditional firewalls. It is based on filtering at the border router the traffic received from the Internet and destined to the IoT network according to the conditions announced by each IoT device. The second is a network access security framework that can be used to control the nodes that have access to the network, based on administrative approval, and to enforce security compliance to the authorized nodes. The third is a network admission control framework that prevents IoT unauthorized nodes to communicate with IoT authorized nodes or with the Internet, which drastically reduces the number of possible security attacks. The network admission control was also exploited as a management mechanism as it can be used to manage the network size in terms of number of nodes, making the network more manageable, increasing its reliability and extending its lifetime.